Dynamical diversity of pulsating solitons in a fiber laser - Chen, Hong-Jie; Tan, Yan-Jie; Long, Jin-Gan; Chen, Wei-Cheng; Hong, Wei-Yi; Cui, Hu; Luo, Ai-Ping; Luo, Zhi-Chao; Xu, Wen-Cheng (Optics express, 2019)
Pulsating behavior is a universal phenomenon in versatile fields. In nonlinear dissipative systems, the solitons also pulsate under proper conditions and show many interesting dynamics. However, the pulsation dynamics are generally concerned with single-soliton cases. Herein, by utilizing real-time spectroscopy technique, namely, dispersive Fourier-transform (DFT), we reveal the distinct dynamical diversity of pulsating solitons in a fiber laser. In particular, the weak to strong explosive behaviors of pulsating solitons, as well as the rogue wave generation during explosions are observed. Moreover, the concept of soliton pulsation is extended to the multi-soliton case. It is found that the simultaneous pulsations of energy, separation and relative phase difference could be observed for solitons inside the molecule, while the pulsations of each individual in a multi-soliton bunch could be regular or irregular. These findings will shed new insights into the complex nonlinear behavior of solitons in ultrafast fiber lasers as well as dissipative optical systems.Pulsating behavior is a universal phenomenon in versatile fields. In nonlinear dissipative systems, the solitons also pulsate under proper conditions and show many interesting dynamics. However, the pulsation dynamics are generally concerned with single-soliton cases. Herein, by utilizing real-time spectroscopy technique, namely, dispersive Fourier-transform (DFT), we reveal the distinct dynamical diversity of pulsating solitons in a fiber laser. In particular, the weak to strong explosive behaviors of pulsating solitons, as well as the rogue wave generation during explosions are observed. Moreover, the concept of soliton pulsation is extended to the multi-soliton case. It is found that the simultaneous pulsations of energy, separation and relative phase difference could be observed for solitons inside the molecule, while the pulsations of each individual in a multi-soliton bunch could be regular or irregular. These findings will shed new insights into the complex nonlinear behavior of solitons in ultrafast fiber lasers as well as dissipative optical systems.